(3eSFhdjI GdehXa GdYGe hMeGjJg aj eUQ hCeQjcG (B/ s - (3MSjf eUWai eMehOs; (3jMj GdLed (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3eSFhdjI GdehXa GdYGe h MeGjJg aj eUQ h CeQjcG h gj GdeSFhdjI GdeOfjI h GdLfGFjI aj cd ef eUQ h CeQjcG ddehXajf GdYehejjf h cPdc LGfH dMeGjI GdOSJhQjI h GdeOfjI h GdLfGFjI h GdJCejfjI h GdGOGQjI aj eUQ CeQjcG aEf GdehXa GdYGe ai GdOhdI GdeYGUQI gh GdCOGI GdCSGSjI ai JMbjb CgOGagG h GdfghV HgG h JSjjQ TFhfgG h dPG MXi GdehXa GdYGe HEgJeGe cHjQs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ(B392 -396.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdehXa GdYGe aj eUQ hCeQjcGs; (3GdcGOQGJ GdNGUIs; (3fXGe GdYGedjf GdeOfjjf HGdOhdIs; (3CYVGA gjFI GdJOQjS HGdLGeYGJs; (3GdhXjaI GdYGeIs; (3GdCYeGd GdeMXhQI Ydi GdehXajf GdYehejjfs; (3GdCYeGd GdeMXhQI Ydi GdehXajf GdYehejjfs; (3GdNWC GdeQabjs; (3Gdhba Yf GdYeds; (3GddhGFMs; (3GdJCOjHs; (3GdOYhi GdJCOjHjIs; (3GdJQbjIs; (3GdEMGdI Edi GdeYGTs; (3GdEMGdI ddJMbjbs; (3GdehXa GdYGe aj eUQ hCeQjcGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2014